Cyclic nucleotide signaling is required during synaptic refinement at the Drosophila neuromuscular junction. Issue 1 (20th June 2016) - Vonhoff, Fernando; Keshishian, Haig
ABSTRACT: The removal of miswired synapses is a fundamental prerequisite for normal circuit development, leading to clinical problems when aberrant. However, the underlying activity‐dependent molecular mechanisms involved in synaptic pruning remain incompletely resolved. Here the dynamic properties of intracellular calcium oscillations and a role for cAMP signaling during synaptic refinement in intact Drosophila embryos were examined using optogenetic tools. We provide In vivo evidence at the single gene level that the calcium‐dependent adenylyl cyclase rutabaga, the phosphodiesterase dunce, the kinase PKA, and Protein Phosphatase 1 (PP1) all operate within a functional signaling pathway to modulate Sema2a‐dependent chemorepulsion. It was found that presynaptic cAMP levels were required to be dynamically maintained at an optimal level to suppress connectivity defects. It was also proposed that PP1 may serve as a molecular link between cAMP signaling and CaMKII in the pathway underlying refinement. The results introduced an in vivo model where presynaptic cAMP levels, downstream of electrical activity and calcium influx, act via PKA and PP1 to modulate the neuron's response to chemorepulsion involved in the withdrawal of off‐target synaptic contacts. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 39–60, 2017